A systematic review and meta-analysis of the diagnosis and surgical management of carcinoid heart disease - Namkoong, Jenny; Andraweera, Prabha H.; Pathirana, Maleesa; Munawar, Dian; Downie, Michael; Edwards, Suzanne; Averbuj, Paula; Arstall, Margaret A. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Carcinoid heart disease (CHD), a complication of carcinoid syndrome (CS), is a rare condition that can lead to right sided valvular heart disease and has been traditionally associated with a poor prognosis. We conducted a systematic review and meta-analysis to explore the accuracy of biomarkers and echocardiography in diagnosing CHD amongst patients who are already known to have neuroendocrine tumours and to assess whether surgical management of CHD leads to a reduction in mortality. Methods: A systematic literature search of MEDLINE, EMBASE, EBM Reviews, Google Scholar, ClinicalTrials.gov was conducted. All studies on patients with carcinoid heart disease (CHD) reporting on biomarkers, echocardiographic and surgical outcomes were included. The National Heart, Lung, and Blood Institute quality assessment tool was used to assess the methodological study quality. Data analysis was performed using Stata Statistical Software and R Studio, and individual meta-analyses were performed for biomarkers, echocardiographic findings, and surgical outcomes. Results: A total of 36 articles were included in the systematic review analysis. N terminal pro-brain natriuretic peptide (NTproBNP) and 5-hydroxyindole acetate (5-HIAA) levels were higher in patients with CHD compared with those without CHD. 32% of CS patients had echocardiographic evidence of cardiac involvement, of which 79% involved tricuspid valve abnormalities. Moderate-severe tricuspid regurgitation was the most common echocardiographic abnormality (70% of patients). However, these analyses had substantial heterogeneity due to the high variability of cardiac involvement across studies. Pooled surgical mortality for CHD was 11% at 1 month, 31% at 12 months and 56% at 24 months. When assessing surgical outcomes longitudinally, the one-month surgical results showed a trend towards more recent surgeries having lower mortality rates than those reported in earlier years, however this was not statistically significant. Discussion: There is not enough data in current literature to determine a clear cut-off value of NTproBNP and 5-HIAA to help diagnose or determine CHD severity. Surgical management of CHD is yet to show significant mortality benefit, and there are no consistent comparisons to medical treatment in current literature.